DIGITAL TEMPERATURE CONTROLLER UNTUK MENGAKTIFKAN FAN DI COOLING TOWER WELDING PLANT 1 DI PT. TOYOTA MOTOR MANUFACTURING INDONESIA - , TRY HATMOKO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Energy saving that is in industry was to be concerned and supervised in production activity. Electric load reduction that any slight have influence in the company activity. PT. Toyota Motor Manufacturing Indonesia was countinuing make improvement to development and efficiency utilization energy. Because of that can influence from cost production, main power, and also environment. Digital Temperature Controller is one of method for Saving energy to control energy which has been used. This tool was succed be made and tested in production activity in welding plant 1 with control cooling fan based on temperature water from residual production. With this tool, can be expected to capable decrease load from energy of electricity, in order can decrease cost of production.